FT-IR Investigation of the Structural Changes of Sulcis and South Africa Coals under Progressive Heating in Vacuum: Correlation with Volatile Matter - Aldo D'Alessio; Anna Maria Raspolli-Galletti; Domenico Licursi; Marco Martinelli (Journal of Combustion)
The analysis of gas evolving during the pyrolysis of two very different rank coals was studied by using FT-IR spectroscopy. These coals, coming from Sulcis (Sardinia, Italy) and from South Africa, respectively, were subjected to progressive heating up to 800°C in vacuum. The thermal destruction of coal was followed by monitoring the production of gases in this range of temperature. The gases evolving in the heating from room temperature to 800°C were collected at intervals of 100°C and analysed by infrared spectroscopy. The relative pressures were plotted against temperature. These graphs clearly show the correlation among qualitative gas composition, temperature, and the maximum value of emissions, thus confirming FT-IR analysis as a powerful key for pyrolysis monitoring.